Intra-oral detection of potent odorants using a modified stir-bar sorptive extraction system in combination with HRGC-O, known as the Buccal Odor Screening System (BOSS). - Büttner, Andrea; Welle, Frank (Flavour and Fragrance Journal, 2004)
The topic of this work was to develop a novel approach that can be used to identify potent odorants intraorally and to determine their dwell time within the oral cavity. The technique, called buccal odour screening system (BOSS), is based on a modiﬁed stir bar sorptive extraction (SBSE) system. It comprises the intra‐oral extraction of odour compounds at deﬁned times after food consumption under optimized in vivo sampling conditions, together with analysis via high resolution gas chromatography–olfactometry (HRGC–O). The obtained analytical data were related to timeresolved retronasal aroma evaluation. This allowed the characterization of prolongued aroma perception elicited after oral aroma application in relation to aroma concentration changes in vivo. For validation of the system, model assays were performed on important aroma compounds in aqueous solutions to ensure sufﬁcient sensitivity of the applied SBSE system under the given extraction conditions. Copyright © 2004 John Wiley & Sons, Ltd.<br